ETA guidelines for the use of levothyroxine sodium preparations in monotherapy to optimize the treatment of hypothyroidism - Marco Centanni; Leonidas Duntas; Ulla Feldt-Rasmussen; Josef Koehrle; Robin P Peeters; Salman Razvi; Pierpaolo Trimboli; Camilla Virili (European Thyroid Journal)
Sodium levothyroxine (LT4) as a monotherapy represents the mainstay of treatment of hypothyroidism, and its use has increased over time. Nevertheless, it faces several potential barriers in its ‘real life’ utilization, and hence its clinical effectiveness may be marred. This is suggested by the frequent situation of patients failing to reach the therapeutic goals of symptom relief and serum TSH control. Thus, an expert task force was approved by the Guidelines Board of the European Thyroid Association to examine the available data and to formulate recommendations based on the available evidence and the experts’ deduction. The task force provides a body of suggestions to optimize the levothyroxine treatment in monotherapy, considering the key point in the individualization of treatment. Furthermore, the nutritional, pharmacological and pathological factors, potentially leading to the increased need for levothyroxine, are discussed, with a specific focus on the use of liquid and softgel formulations of the hormone.